2018
DOI: 10.3168/jds.2017-14267
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vaccination with a Klebsiella pneumoniae siderophore receptor protein vaccine for reduction of Klebsiella mastitis in lactating cattle

Abstract: Clinical mastitis caused by Klebsiella spp. is an emerging problem in the US dairy industry and results in a high degree of financial losses to dairy workers. This study was conducted as a randomized, blinded, and placebo-controlled efficacy study of a Klebsiella pneumoniae siderophore receptor protein (SRP) vaccine (Kleb-SRP), with a total of 569 cows and heifers enrolled. The study was designed to look at vaccine effect on Klebsiella mastitis; however, the SRP in Klebsiella are highly conserved across colifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…These herds used bacterin core-antigen vaccines intended to reduce mastitis due to E. coli, and the recent introduction of Klebsiella-specific mastitis vaccines in the United States suggests a need to investigate the effects of immunization on the frequency of these costly negative outcomes. Gorden et al (2018) reported that a Kleb. pneumoniae siderophore receptor protein vaccine increased milk production by 1.74 kg/d and reduced SCC by 64.8% in one herd when cows were vaccinated before calving, compared with cows that did not receive the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…These herds used bacterin core-antigen vaccines intended to reduce mastitis due to E. coli, and the recent introduction of Klebsiella-specific mastitis vaccines in the United States suggests a need to investigate the effects of immunization on the frequency of these costly negative outcomes. Gorden et al (2018) reported that a Kleb. pneumoniae siderophore receptor protein vaccine increased milk production by 1.74 kg/d and reduced SCC by 64.8% in one herd when cows were vaccinated before calving, compared with cows that did not receive the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…A K. pneumoniae vaccine (Kleb-SRP) was prepared by purifying siderophore receptor and porin proteins from fermentation cultures of K. pneumonia. Subcutaneous vaccination of cows with Kleb-SRP before calving decreased the risk of Klebsiella and total coliform mastitis by 76.9% and 47.5%, respectively (Gorden et al, 2018).…”
Section: Klebsiella Pneumoniamentioning
confidence: 98%
“…Administration of cows with the vaccine before calving significantly decreased the risk of Klebsiella and total coliform mastitis by 76.9% and 47.5% respectively. (Gorden et al, 2018)…”
Section: Campylobacter Jejuni Cframentioning
confidence: 99%
“…Their preparation of DNA vaccines expressing OmpA and OmpK36 proteins protected mice, with intradermal vaccination inducing better protection than when these vaccines were given by the intramuscular (IM) route [89]. A KP siderophore receptor protein veterinary vaccine (Kleb-SRP) reduced the incidence of KP bovine mastitis and increased milk production when administered before calving [90].…”
Section: Toxins-in 1983mentioning
confidence: 99%